Analysis of Students' Critical Thinking Disposition in Science Learning - Verawati, Ni Nyoman Sri Putu; Rokmat, Joni; Sukarso, AA; Harjono, Ahmad; Makhrus, Muh. (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
The study aimed to analyze the specific dispositions that contribute to effective critical thinking among prospective science students. Utilizing a descriptive survey method, the study involved 52 participants from different universities, aiming to gather comprehensive data on their critical thinking dispositions. The research instrument, a structured questionnaire comprising 36 items derived from Ennis's critical thinking indicators, was validated and tested for reliability, ensuring its efficacy in measuring the intended constructs. The findings revealed that the overall critical thinking disposition of the students was predominantly below the critical threshold, with significant variability across different indicators. For instance, indicators such as seeking and offering clear statements and reasons scored relatively high, while others like taking into account the total situation scored lower. This disparity highlights the need for targeted interventions to enhance specific critical thinking dispositions. The study recommends integrating contextual and inquiry-based learning approaches, which have been shown to effectively foster critical thinking by engaging students in real-world problem-solving scenarios. Moreover, incorporating collaborative and experiential learning experiences can further nurture critical thinking skills, promoting deeper understanding and innovation. The research emphasizes the importance of developing specific disposition like open-mindedness to improve the critical thinking capabilities of prospective science teachers, ultimately enhancing their academic performance and preparedness to tackle complex scientific issues.